Religious Tourism and Pilgrimage Festivals Management: An International Perspective - Raj, Razaq (CABI, 2014)
Undoubtedly, this book has compelling appeal for emerging and growing academic audiences within Asia and South Asia and the Indian subcontinent, as well as for fields of study within the West, which focus on the ever-increasingly important societal narratives of the ‘sacred and secular’, and the application of these narratives to the activities of tourism and events. Theoretical and empirical perspectives on travel, religion, pilgrimage and the celebration of festivals and events are supported by case studies that express either personal perspective on religious devotion or research insights into the relationships between religion and tourism